Polymorphous Low-Grade Neuroepithelial Tumor of the Young (PLNTY): Molecular Profiling Confirms Frequent MAPK Pathway Activation. Issue 9 (7th August 2021) - Ida, Cristiane M; Johnson, Derek R; Nair, Asha A; Davila, Jaime; Kollmeyer, Thomas M; Minn, Kay; Fadra, Numrah M; Balcom, Jessica R; Fung, Kar-Ming A; Kim, Dong Kun; Kaufmann, Timothy J; Kipp, Benjamin R; et al.
Abstract: Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a recently described epileptogenic tumor characterized by oligodendroglioma-like components, aberrant CD34 expression, and frequent mitogen-activated protein kinase (MAPK) pathway activation. We molecularly profiled 13 cases with diagnostic histopathological features of PLNTY (10 female; median age, 16 years; range, 5–52). Patients frequently presented with seizures (9 of 12 with available history) and temporal lobe tumors (9 of 13). MAPK pathway activating alterations were identified in all 13 cases. Fusions were present in the 7 youngest patients: FGFR2-CTNNA3 (n = 2), FGFR2-KIAA1598 ( FGFR2-SHTN1 ) (n = 1), FGFR2-INA (n = 1), FGFR2-MPRIP (n = 1), QKI-NTRK2 (n = 1), and KIAA1549-BRAF (n = 1). BRAF V600E mutation was present in 6 patients (17 years or older). Two fusion-positive cases additionally harbored TP53 / RB1 abnormalities suggesting biallelic inactivation. Copy number changes predominantly involving whole chromosomes were observed in all 10 evaluated cases, with losses of chromosome 10q occurring with FGFR2-KIAA1598 ( SHTN1 )/ CTNNA3 fusions. The KIAA1549-BRAF and QKI-NTRK2 fusions were associated respectively with a 7q34 deletion and 9q21 duplication. This study shows that despite its name, PLNTY also occurs in older adults, who frequently show BRAF V600E mutation. It also expands the spectrum of the MAPK pathway activating alterations associated with PLNTY and demonstrates recurrent chromosomal copy number changes consistent with chromosomal instability.